Pengaruh Kepemimpinan Guru dan Kemampuan Berkomunikasi Guru terhadap Motivasi Belajar Siswa pada Mata Pelajaran Ekonomi - Ningsi, Sri; Hafid, Radia; Sudirman Sudirman; Bahsoan, Agil; Maruwae, Abdulrahim (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to discover the influence of teacher leadership and teacher communication skills on students' learning motivation in the Economics subject among tenth-grade students at SMA Negeri 1 Momunu, Buol Regency, Central Sulawesi Province. The study employed a quantitative approach using a descriptive study method. Primary data were collected by distributing questionnaires to tenth-grade students at SMA Negeri 1 Momunu, Buol Regency, Central Sulawesi Province. The total population consisted of 128 students, and a sample of 56 respondents was selected using simple random sampling. Data analysis was conducted using multiple linear regression with the assistance of SPSS 21 software. The results of the study indicate that: (1) Teacher leadership has a positive and significant influence on students' learning motivation in Economics subject; (2) Teacher communication skills also have a positive and significant influence on students' learning motivation; and (3) Teacher leadership and communication skills simultaneously have a significant influence on students learning motivation in the Economics subject. This is supported by the coefficient of determination (R Square) value of 0.458, which means that 45.8% of the variance in students' learning motivation can be explained by teacher leadership and communication skills. In other words, Improved teacher leadership and communication skills are positively associated with increased student motivation in learning the Economics subject among tenth-grade students at SMA Negeri 1 Momunu, Buol Regency, Central Sulawesi Province. Therefore, it is important for teachers to continuously develop their leadership qualities and communication abilities as integral components of an effective and motivating learning environment. The remaining 54.2% is influenced by other variables not examined in this study.